KOMPETENSI GURU SOSIOLOGI DI SMA NEGERI SE-KABUPATEN HULU SUNGAI TENGAH - Ulpah Ulpah (Universitas Lambung Mangkurat, 2015)
Teachers competence consists of pedagogical competence, personality competence, social competence, and professional competence which can be obtained through professional education. As a matter of fact, in the field, teachers competence is still low, especially in arranging lesson plans. From the result of pre-research, it was found that only 40% of teachers can make good lesson plans, and 30% of teachers able to teach in varying methods. Therefore, the purpose of this research was to describe the competence of Sociology teachers in Senior High Schools in Hulu Sungai Tengah Regency determined from the aspects of Sociology teachers competence, namely pedagogical competence, professional competence, personality competence, and social competence. This research method applied a descriptive qualitative method. The use of this method is to obtain the most complete and detail, credible and also meaningful data. The decriptive data was obtained from many sources, consisted of oral form, text/written form and direct observation in finding out the competence of Sociology teachers in teaching learning process activity. Finally, it was obtained the actual and detail information about Sociology teachers competence in Senior High Schools of HST Regency. The research found that pedagogic competence of Sociology teachers in Senior High School of HST Regency was 2.9 or 74 which can be classified in average. The professional competence was 2.8 or 71 which can be included in good. The personality competence was 3.7 or 92 which belonged to excellent. Finally, the social competence of the teachers was 3.1 or 76 which categorized as good. Based on the result of this research, it is suggested for the Sociology teachers to improve their pedagogical competence, personality competence, professional competence and social competence.Key Word: teachers competencies, sociology matter, and competencies aspect